Environmental and socio-demographic individual, family and neighborhood factors associated with children intestinal parasitoses at Iguazú, in the subtropical northern border of Argentina. - Maria Romina Rivero; Carlos De Angelo; Pablo Nuñez; Martín Salas; Carlos E Motta; Alicia Chiaretta; Oscar D Salomón; Song Liang (Public Library of Science (PLoS), 2017)
Intestinal parasitoses are a major concern for public health, especially in children from middle and low-income populations of tropical and subtropical areas. We examined the presence and co-infection of parasites in humans as well as parasitic environmental contamination in Puerto Iguazú, Argentina. We explored the environmental and socio-demographic characteristics of the persistence of parasites in children and their environment.This cross-section survey was conducted among children population comprised into the area of the public health care centers of Iguazú during June 2013 to May 2016. Copro-parasitological status of 483 asymptomatic children was assessed. Simultaneously, a design-based sampling of 744 soil samples and 530 dog feces was used for characterize the environmental contamination. The 71.5% of these sites were contaminated. Sixteen genera were detected in the environment being hookworms (62.0%) the main pathogens group detected followed by Toxocara spp (16.3%), Trichuris spp (15.2%) and Giardia (6.5%). Total children prevalence raised 58.8%, detecting twelve genera of parasite with Giardia intestinalis as the most prevalent pathogen (29.0%) followed by Enterobius vermicularis (23.0%), Hymenolepis nana (12.4%) and hookworms (4.4%). Through questionnaires and census data, we characterized the socio-demographics conditions at an individual, family and neighborhood levels. A multi-level analysis including environmental contamination data showed that the ´presence of parasites´ was mostly determined by individual (e.g. age, playing habits, previous treatment) and household level (e.g. UBN, WASH, mother's literacy) determinants. Remarkably, to define the level of 'parasite co-infection', besides individual and household characteristics, environmental factors at a neighborhood level were important.Our work represents the major survey of intestinal parasites in human and environmental samples developed in the region. High prevalence was detected in the children population as well as in their environment. This work shows the importance of considering and promoting multi-level actions over the identified determinants to face this public health problem from integrative approaches.